2016
DOI: 10.1016/j.cellsig.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-3 mediates HIV-1 transactivation via NFκB and JNK pathways and histone acetylation, but prolonged activation suppresses Tat and HIV-1 replication

Abstract: TLR3 has been implicated in the pathogenesis of several viral infections, including SIV- and HIV-1-induced inflammation and AIDS. However the molecular mechanisms of these TLR3-mediated effects are not known, and it is not known whether HIV interacts with cellular TLR3 to affect disease process. Here we investigate the effects of TLR3 ligands on HIV-1 transactivation using both primary human macrophages and cells containing integrated copies of the HIV-1 promoter. We demonstrate that TLR3 activation induced up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 53 publications
3
37
0
Order By: Relevance
“…We further show the effects of TLR3 ligands on HIV-1 transactivation and transcription factors involved in HIV-1 replication. This article complements the data reported by the authors, “Toll-Like receptor-3 mediates HIV-1 transactivation via NFκB and JNK pathways, and histone acetylation, but prolonged activation suppresses Tat and HIV-1 replication” (Bhargavan et al, 2015) [1] , and the interpretation of these data can be found in the research article published by the authors in Cellular Signaling in 2015 (Bhargavan et al, 2015) [1] .…”
supporting
confidence: 79%
See 2 more Smart Citations
“…We further show the effects of TLR3 ligands on HIV-1 transactivation and transcription factors involved in HIV-1 replication. This article complements the data reported by the authors, “Toll-Like receptor-3 mediates HIV-1 transactivation via NFκB and JNK pathways, and histone acetylation, but prolonged activation suppresses Tat and HIV-1 replication” (Bhargavan et al, 2015) [1] , and the interpretation of these data can be found in the research article published by the authors in Cellular Signaling in 2015 (Bhargavan et al, 2015) [1] .…”
supporting
confidence: 79%
“…Human MDM were obtained from freshly elutriated human monocytes as previously described [1] , [2] , cultured in 6-well plates (2 million cells per well), and treated with 10 or 25 μg/ml PIC for 2–120 h, with each experimental condition performed in triplicate. In separate experiments, MDM were infected with HIV-1 ADA at a multiplicity of infection of 0.01 as previously described [1] , [2] , [3] , [4] , with or without PIC treatment (10 and 25 µg/ml) for 2–120 h, with each experimental condition performed in triplicate. Following treatment, cells were harvested, total RNA was extracted using the Trizol reagent, and real-time PCR performed as described in the main manuscript [1] .…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This data suggested that activated TLR3 pathways were responsible for the production of key pro-inflammatory cytokines and chemokines in IAV infected mast cells. A recent study suggested that TLR3 could act as viral sensor to mediate viral transactivation via upregulation of transcription factors such as c-Jun, which was known to regulate the viral promoter activity (Bhargavan et al, 2016). We recently also showed that IAV infection up-regulated c-jun expression and activation (Xie et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Data revealed that Tat-AG had marginal effects on the blood-brain barrier, whereas Tat-B induced transcriptional upregulation of proinflammatory chemokines, complement components C3, C7, and factor-B, matrix metalloproteinases (MMP)-3, MMP-10, MMP-12; and also increased the activity of these MMPs in a dose-dependent manner (Woollard et al, 2014). Additionally, preliminary data also showed increased replication and transactivation of HIV-1 CR02_AG in macrophages that was associated with increased acetylation of histone proteins and histone acetyl transferase activity (Bhargavan et al, 2016). More studies in HIV infected individuals from Cameroon are underway to shed light on the effects of HIV subtype on viremia and neurocognitive impairment.…”
Section: Effects Of Hiv Subtype Diversity On Handmentioning
confidence: 99%